Metode Analisis Risiko Kerusakan Mesin Produksi di Indonesia: Literature Review - Pamungkas, Iing; Irawan, Heri Tri; Basuki, Mahmud; Ridha, Arrazy Elba; Adib, Adib; Syahputra, Rizki Agam; Widarta, Fajar Okta (xxxx-xxxx, 2023)
Production machines are specially designed to perform various tasks such as processing, assembly, packaging and more depending on the type of production and the industry involved. However, damage to production machines is unavoidable with such a task. Machine damage can occur due to various factors, such as excessive use, inadequate maintenance, worn components, design errors and many more. Damage to the machine certainly raises risks, both measurable risks and immeasurable risks. The risk of machine failure can have a serious impact on the productivity, reliability and operating costs of a business. The use and application of risk analysis methods or approaches can be used to minimize the occurrence of excessive risk. The purpose of this research is to find out various methods of risk analysis of production machine damage in various industries in Indonesia. This research uses a systematic method by reviewing the literature from various published articles which are then identified and analyzed which focus on various production machine damage risk methods used in various industries in Indonesia. The results of the study show that there are several methods of analyzing the risk of damage to production machines that are commonly used in Indonesia, such as failure mode and effect analysis (FMEA, FMECA, fuzzy FMEA), risk based maintenance (RBM), fault tree analysis (FTA), fishbone diagram, enterprise risk management (ERM), failure tracking matrix (FTM), total quality control (TQM), logic tree analysis (LTA), overall equipment effectiveness (OEE), Hazard operability (Hazop), and certainty factor and forward chaining. Some of these methods are generally integrated with various other methods or approaches to obtain optimal results.